Creative methods in teaching art:nuances between the utopian and the vital (Revista Apotheke, 2024)
This article discusses creative learning practices, observed in the Teaching Internship discipline, in the master’s course of the Postgraduate Program in Art - PPGA UFES. The research described in this text presentes teaching methods based on creativity and art creation processes. Inspired by the utopian projects of artists Ilya and Emilia Kabakov (1998-2018), the methodological paths are developed in dialogue with the creative activators of the author David de Prado Díez (1987). In this sense, paths are traced through the Creative Problem Solving method towards a vital pedagogical approach.
Keywords: creative learning; creative process; creative activators; utopian projects; art education